NATURAL CONDITIONS AND ISSUES OF LAND RESOURCES IN THE TRADITIONAL MANAGEMENT OF THE INDIGENOUS POPULATION OF THE ARCTIC REGIONS OF YAKUTIA IN THE FIRST POST-SOVIET PERIOD - Sannikova, Yana Mikhailovna (Bulletin Social-Economic and Humanitarian Research, 2022)
The article considers the natural conditions and issues of land resources in the traditional management of the indigenous population of the studied region. The first post-Soviet period in Yakutia, the study of its Arctic and northern territories, contributed its own features to the formation of the land fund. In this regard, agricultural lands included, in addition to agricultural lands, deer and horse pastures. And although there was no universal centralized accounting of them at that time, using the example of farms in areas of traditional residence of indigenous small-numbered peoples of the North, it is possible to show the distribution of land and the specifics of land use depending on the specialization of the districts. At the same time, land resources based on the data of uluses/districts are shown with the determination of the number of villages and settlements by groups of areas of specialization and traditional branches of economy. The considered statistical data provide research material for further study of the problem of the development of traditional economy in Yakutia.